The Mediating Role of Occupational Commitment in the Effects of Work–Family Conflict on Intention to Leave - Merve Koçoğlu Sazkaya; Zeynep Görmezoğlu (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: It is important to increase the occupational commitment of nurses who experience work-family conflict to decrease their intention to leave.Aim: This study’s aim was to demonstrate the role of occupational commitment in the effects of work–family conflict on the turnover intention of nurses during the COVID-19 pandemic.Method: This descriptive study was conducted with 390 nurses working in two different hospitals of a foundation university in Istanbul.Results: The results of this study showed that there was an effect of work–family conflict on intention to leave (r2 = 0.19; p lt; 0.05) and occupational commitment (r2 = 0.01; p lt; 0.05). Another result of the research is that occupational commitment also affected the intention to leave (r2 = 0.24; p lt; 0.05). In addition, according to the results of the mediation analysis carried out to test the hypothesis of the research, there was a mediating effect of occupational commitment since the β coefficient of nurses' perceptions of work-family conflict in the first stage was 0.43, while it decreased to 0.40 in the third stage. This result showed that occupational commitment had a mediating role in the effects of work–family conflict on the intention to leave.Conclusion: This study showed that occupational commitment had a mediating role in the effects of work–family conflict on the intention to leave. According to the research results, although nurses experience work–family conflict due to working conditions during the COVID-19 pandemic, their occupational commitment decreases their intention to leave.